Tinjauan Makna Pada Label Korek Api Propaganda Jepang Di Indonesia Tahun 1942-1945 - Lintang Dewi Prasistiya; Donna Carollina (AKSA: Jurnal Desain Komunikasi Visual, 2019)
Japanese propaganda matchboxes is one of the propaganda media used by Japan in its effort to get the hearts and attention of Indonesian people. This matchbox is producted on 1942-1945 with varied themed on each series, this research will spesifically discuss about series 101. As a propaganda media, this matchbox unconsciously is one of visual communication design product from the illustration, message delivery to the audience through design and its own function as a packaging. Thus, this research was conducted to reveal the meaning behind the design of the Japanese propaganda matchbox series 101. The research of meaning in this qualitative research is carried out with an approach to art critism according to Edmund Burke Feldman. The result of this research is the design of Japanese propaganda matchbox series 101 was produced in 1994 and designed by Takashi Kono. If assessed in term of quality, the visual element in this lable is harmoniously arranged and create a balanced and unified design. The color has a high contrast, the typography used is san-serif which has high readability and legibility, and the object of illustration is made as closely as possible to the actual object so it can be easily understood. All the visual elements displayed on the design has a connection with the main theme and purpose of this matchbox label is to restore Indonesian people trust because on 1944, Japan situation in battlefield is getting worse and there’s a rumor that Japan has defeated in the war, with some hope that they will get Indonesian people trust again and Indonesian people have some initiative to help Japan in the war. Compare to the previous series of the matches, this series emphasize the atmosphere of war and victory in war over America, Britain and China.